1987
DOI: 10.1192/bjp.151.3.404
|View full text |Cite
|
Sign up to set email alerts
|

De Clérambault's Syndrome in Organic Affective Disorder

Abstract: Two patients with erotomania (de Clérambault's syndrome) associated with epilepsy and head trauma are presented. The delusion appeared during periods of mania or hypomania and partially remitted during depression or euthymia. Erotomania may be seen in a wide variety of psychotic conditions, including those that are organically based.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 3 publications
1
7
0
1
Order By: Relevance
“…The delusion is often intense and particularly difficult to treat. Erotomanic delusions have been reported in patients with Alzheimer's disease (Drevets 1987;Carrier 1990), affective disorders (Signer & Cummings 1987a;Signor & Swinson 1987), and schizophrenia (Hayes & O'Shea 1985). It has also been reported to occur in the absence of all other psychopathology, that is, independent of any other disorder.…”
Section: Introductionmentioning
confidence: 99%
“…The delusion is often intense and particularly difficult to treat. Erotomanic delusions have been reported in patients with Alzheimer's disease (Drevets 1987;Carrier 1990), affective disorders (Signer & Cummings 1987a;Signor & Swinson 1987), and schizophrenia (Hayes & O'Shea 1985). It has also been reported to occur in the absence of all other psychopathology, that is, independent of any other disorder.…”
Section: Introductionmentioning
confidence: 99%
“…He divided the condition into a primary form that begins suddenly, involves one love object, and is usually chronic, and a secondary form that begins insidiously, involves multiple love objects, and is recurrent. Erotomania has been associated with traumatic brain injury, subarachnoid hemorrhage, seizure disorders, Alzheimer's disease, vascular dementia, and frontotemporal dementia with motor neuron disease (7)(8)(9)(10)(11)(12). Subsequent case series (2)(3)(4)(5)(6) have suggested that erotomania is a rare illness usually seen in individuals in their late 30s to mid-40s.…”
mentioning
confidence: 99%
“…They usually manifest varying combinations of a slower onset of symptoms, a less stable course, other persecutory and sometimes bizarre delusions, and multiple love objects. Signer & Cummings (1987b) showed that a significant mood change is invariably present. The site and exact nature of the organic factor may colour the picture further.…”
Section: Discussionmentioning
confidence: 99%